Precise Blood Glucose Sensing by Nitrogen-Doped Graphene Quantum Dots for Tight Control of Diabetes. (17th July 2021) - Mousavi, Seyyed Mojtaba; Hashemi, Seyyed Alireza; Gholami, Ahmad; Mazraedoost, Sargol; Chiang, Wei-Hung; Arjmand, Omid; Omidifar, Navid; Babapoor, Aziz
Abstract : Graphene quantum dots (GQD) are novel fluorescent carbon nanomaterials based on a graphite structure. Thanks to extraordinary properties such as high surface area and enhanced prevalent optical properties, they have received more interest for special applications. Glucose sensing is a critical factor for the diagnosis, and treatment of diabetes plays an important role and could contribute to the monitoring of diabetes and other related parameters, which has been effectively underscoring the health society. Detecting glucose has been cultivated through different systems, for example, electrochemical or optical techniques. Novel transducers made with GQD that fluorescent coordinate methods have considered the improvement of cutting-edge glucose sensors with prevalent affectability and accommodation. Currently, detection of glucose by nitrogen-doped GQD frameworks concerning the determined objectives has been considerably considered. Here, we explored the properties of fluorescent nitrogen-doped GQD as an excellent and effective index that significantly could promote nitrogen-doped GQDs and make them an appropriate candidate for detecting glucose.